Lead Contamination In Soil Of Yogyakarta City, Indonesia - Wawan Budianta (Geological Engineering Department Universitas Gadjah Mada, 2015)
This paper investigates on Pb concentrations and mobility in soil of overall Yogyakarta City, Indonesia. The objectives of this study include to investigate Pb concentrations in the surface soil throughout Yogyakarta and to study their possible sources and potential environmental impacts. The soil samples from 168 locations in Yogyakarta was obtained, representing different land use and traffic conditions. Spatial analysis and sequential extraction analysis were performed. Generally, contour pattern of Pb value clearly shows that high value is concentrated in the middle and few north part of the study area, confirmed by traffic condition in the study area. In general, the results of sequential extraction analysis shows that Pb was predominantly associated with exchangeable fraction. The presence of lead in the exchangeable fractions may pose a serious environmental concern since they are highly soluble and potentially bio-available in the soil of study area. Keywords: Soil, lead contamination, GIS, sequential extraction.